Ecóico e nomeação de figuras em crianças com deficiência auditiva pré-lingual com implante coclear - Souza, Fabiana Cristina de [UNESP]; Bevilacqua, Maria Cecília; Verdu, Ana Claudia Moreira Almeida [UNESP] (My University, 2013)
The aim of this work was to verify the effect of teaching the echoic behavior over the pictures naming in four children between eight and nine years old with prelingual hearing impaired, users of cochlear implants. The design adopted was: (a) pre-training that taught the matching-to-sample task; (b) pre-tests that selected three words to teach; (c) teaching of auditory-visual conditional relations; (d) naming pos-test; (e) the teaching of echoic with orofacial clues and, (f) the second naming pos-test. In the pre-test all participants achieved smaller percentage of correct on naming (60%-80%) and echoic (20%-50%) when compared to percentages word recognition (86%-93%). All participants learned the auditory-visual relations. The improvement on naming test occurred after auditory training select based for two participants; for other two participants the improvement on naming test occurred just after the training of echoic. Analysis of data showed that the listening and speaking performances are independent in their establishment and require specific conditions of teaching; in the case of this study, even though the result is not generalized to all participants, the highest correspondence into point to point naming was obtained following the teaching of echoic.

O objetivo deste trabalho foi verificar o efeito do ensino do comportamento ecoico sobre a nomeação de figuras em quatro crianças entre oito e nove anos de idade, com deficiência auditiva pré-lingual e usuárias de implante coclear. O delineamento adotado foi: (a) pré-treino que ensinou a tarefa de matching-to-sample; (b) pré-teste que selecionou três palavras para ensino; (c) ensino de relações condicionais auditivo-visuais; (d) pós-teste de nomeação; (e) ensino de ecoico com pistas orofaciais e, (f) segundo pós-teste de nomeação. No pré-teste todos os participantes demonstraram menores porcentagens de acertos em nomeação (60%-80%) e em ecoico (20%-50%), se comparadas a reconhecimento de palavras (86%-93%). Todos os participantes aprenderam as relações auditivo-visuais. A melhora em nomeação ocorreu depois do treino baseado em seleção para dois participantes; para outros dois, somente ocorreu depois do treino de ecoico. A análise dos dados demonstrou que os desempenhos de falante e de ouvinte são independentes e seu estabelecimento requer condições específicas de ensino; no caso deste estudo, embora o resultado não seja generalizado para todos os participantes, a maior correspondência ponto a ponto em nomeação foi obtida após o ensino de ecoico.
Echoic and picture naming in prelingual impaired hearing children with cochlear implant
Keywords: Pictures naming; Auditory-visual teaching; Echoic teaching; Impaired hearing; Cochlear implant user; Nomeação de figuras; Ensino auditivo-visual; Ensino de ecoico; Deficiência auditiva; Usuário de implante coclear